Role of Human Resource Management in Governance on the Growth of Collective Entrepreneurship in the Agriculture Sector, Kenya - makongoso, meshack okoth; Gichira, Robert; Orwa, George Otieno (Advances in Social Sciences Research Journal, 2015)
Agricultural cooperatives, as member-owned and controlled agribusiness enterprises play an important role in upgrading socio-economic status of members, however, they experience a myriad of hitches including mismanagement and inadequate innovation raising questions about quality of governance. The concern is legitimacy of boards, scanty expertise and effectiveness of managers in supervising and protecting members. They are practical example of collective entrepreneurship but pay little attention to entrepreneurship and seldom enhance their business dimensions through it for competitiveness. They decline in performance due to poor governance, weak capability building and human resource management practices. There is inadequate research on the role of human resource management in governance on the collective entrepreneurship in agriculture sector. The study sought to investigate the role of human resource management in governance on the growth of collective entrepreneurship in the agriculture sector. A descriptive research was adopted where multi-stage sampling technique and questionnaire was used to collect data from selected respondents in the coffee cooperatives in Kenya. Data were analysed using multiple regression statistical method. It was found that human resource management positively influence the growth of collective entrepreneurship and policy strongly mediates relationship between them. The study recommended implementation of strategic human resource management practice to enhance the agricultural cooperatives’ level of progress and performance since functional human resources management affected only individual performance and turnover. Key words: governance, human resource management, growth, collective entrepreneurship, agricultural cooperatives